Kidney Injury Molecule-1 (KIM-1): A specific and sensitive biomarker of kidney injury - Bonventre, Joseph V. (Scandinavian journal of clinical & laboratory investigation. Supplement, 2008)
There is an urgent need for the detection and monitoring of kidney injury in both the acute and chronic disease setting. Urinary kidney injury molecule-1 (Kim-1), a type-1 transmembrane protein, is not normally present, but is expressed on the proximal tubule apical membrane with injury. Kim-1 has proved to be an outstanding indicator of kidney injury in the rat, outperforming blood urea nitrogen and serum creatinine as predictors of histopathological changes in the proximal tubule in response to many pathophysiological states or toxicants. Studies in man indicate that tissue expression and urinary excretion of the ectodomain of KIM-1 are sensitive and specific markers of injury as well as predictors of outcome.